Review: Soil Electrical Characteristics Under High Impulse Currents - Nor, Normiza Mohamad (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2006)
This paper aims to extensively review, discuss, and compare the published studies on soil behavior under high currents, based on field tests, laboratory tests, and computational methods, conducted by previous authors from 1928 to 2003. The paper presents an informative review on soil electrical characteristics under high impulse currents as well as a useful list of references for researchers on nonlinear soil behavior.